Pass the Praxis II test : principles of learning and teaching - Shorall, Christina Paparozzi (Boston, Mass : Pearson, 2009)
Lists more than 1500 institutions of higher education and other organizations involved in the field of educational and training technology. Each entry contains information on areas of interest, current and future projects and publications. It is indexed by key word and institution
Includes bibliographical references
Keywords: Teachers. -- Study guides. -- Examinations -- United States; National teacher examinations -- Study guides -- United States